The Effect of Ignition Timing on Combustion of Ammonia/Ethanol Mixtures in Spark-Assisted Compression Ignition Engine with a Sub-chamber - Okada, Takanobu; Ichiyanagi, Mitsuhisa; Yilmaz, Emir; Suzuki, Takashi; Shiraishi, Hikaru; Ngwompe Souop, Eric Le Roy; Widjaja, Evan; Sutedjo, Jason; Marcelo, Christian Dennis; Tjiotijono, Ferdinand Ronaldo; Gotama, Gabriel Jeremy; Anggono, Willyanto (Journal of Engineering and Technological Sciences, 2025)
Carbon dioxide (CO2) is the primary contributor to greenhouse gas emissions. Ammonia (NH3) has emerged as a promising alternative fuel due to its high energy density, ease of transportation, and carbon-free molecular structure. However, its practical application is challenged by slow combustion characteristics and high ignition temperatures. This study investigates the combustion behaviour of ethanol-ammonia mixtures using a high-compression-ratio engine (17.7:1) equipped with a sub-chamber. The engine operated at a constant speed of 1000 rpm. Ammonia energy ratios of 40%, 50%, and 60% were tested across ignition timings of 0°, 2°, 4°, 6°, and 8° crank angle (CA) before top dead center (BTDC). Results indicate that advancing the ignition timing increases in-cylinder pressure and heat release rate while reducing combustion duration. Lower ammonia energy ratios yielded higher thermal efficiency. Conversely, higher ammonia content and advanced ignition timings led to increased NOx emissions.